MSMEs Development of The Minahasa Spice House Through Re-Branding, Logos And Digital Marketing: Pengembangan UMKM Rumah Rempah Minahasa Melalui Re-Branding, Logo dan Digital Marketing - M. Rizky Pradana Novianto Putra; Sulastri Irbayuni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This article discusses the redesign of the branding design of Rumah Rempah Minahasa. Re-branding functions as a tool for product attributes and building identity, due to increasing competition between competitors. Minahasa Spice House is the name of the Tumaluntung MSME, Airmadidi, North Minahasa Regency, North Sulawesi Province. Moving into the world of spices. Minahasa Spice House produces spices, namely nutmeg and cloves. It doesn't yet have a definite logo and brand name, which is easily recognized by the public. This Minahasa Spice House still carries out traditional marketing and promotions. This service activity carried out re-branding and created a logo according to the wishes of the MSME owner, as well as creating Instagram and Tiktok social media accounts for digital marketing.